STOMATA INDEX OF Syzygium oleana AS AN ENRICHMENT MATERIAL FOR PHOTOSYNTHESIS SUBCONCEPT - Noor Syifa; Sri Amintarti (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Syzygium oleana is easy to find in the campus area, which can be found on roadsides, parking areas, and campus grounds. This study aims to (1) describe the stomata index on the leaves of Syzygium oleana at Universitas Lambung Mangkurat, (2) to describe the validation of handout teaching materials, and (3) to describe the practicality of the content of the handout teaching materials. This study uses descriptive research methods to collect data in the field and further research results are developed in the form of teaching materials in the form of handouts using development research methods according to Tessmer. Based on the results of the study, it was found that the sampling area showed varying stomatal indices. Variations in the stomatal index results obtained are influenced by the intensity of sunlight. The results of the validation handout developed were declared valid from the average assessment of 2 experts with an average validity score of 75.83%. The results of the practicality test of the contents by 4 students obtained the result that is 82.46% so that it can be categorized as practical.